The Implementation of Toddler Public Health Center During The Covid-19 Pandemic: A Scoping review - Nur Laeli Rokhmah; Mufdlillah Mufdlillah; Enny Fitriahadi (International Journal of Health Science and Technology, 2021)
Public Health Center shows some decreases in health service during Covid 19 Pandemic. This scoping review aims to review evidence related to the implementation of PHC during Covid-19 Pandemic. This paper adopted Arksey O'Malley framework consisting of five stages: identifying scoping review questions and relevant articles; searching for articles, conducting charting data; compiling, summarizing and reporting results. This paper reviewed 6 articles. Three themes were obtained: the role of cadres; barriers; and innovations at PHC. The results conclude that the practice of PHC in Indonesia does not accomodate the community need adequately yet. Therefore it s necessary to evaluate PHC activities and improve partnership with community and related stakeholders